Essentials of college algebra - Lial, Margaret L.; Hornsby, E. John; Schneider, David I. (Pearson Education Limited, 2015)
Steadfast Support for Your Evolving Course. Essentials of College Algebra, Eleventh Edition, by Lial, Hornsby, Schneider, and Daniels, develops both the conceptual understanding and the analytical skills necessary for success in mathematics. With the Eleventh Edition, the authors have adapted and updated the program for the evolving student, New co-author Callie Daniels brings her experience with traditional, hybrid, and online courses, to create a suite of resources to support today's learners. This program provides a better teaching and learning experience-for you and your students